The Effect of Servant Leadership and Compensation on Employee Engagement Makassar City Tourism Office - Andi Batary Citta; Guntur Suryo Putro; Arfiany Arfiany; Akmal Syam (Transpublika Publisher, 2025)
This study investigates the impact of servant leadership and compensation on employee engagement at the Makassar City Tourism Office in Indonesia. The research addresses a critical gap in understanding how leadership style and compensation strategies affect employee engagement within public sector tourism organizations. Using a quantitative methodology, the study collected data from 50 employees through a mixed-method approach incorporating questionnaires, direct observations, and interviews. Statistical analysis revealed that servant leadership has a significant positive influence on employee engagement, demonstrating that leadership approaches focused on serving and supporting employees can enhance their workplace commitment and involvement. Similarly, compensation was found to have a substantial positive effect on employee engagement, confirming that both financial and non-financial rewards play crucial roles in fostering employee motivation and dedication. The findings provide practical implications for public sector organizations, particularly in tourism management, suggesting that the implementation of servant leadership principles combined with effective compensation strategies can create an optimal work environment that promotes higher levels of employee engagement. This research contributes to the growing body of literature on public sector management and offers valuable insights for policy makers and organizational leaders seeking to enhance workforce engagement in government tourism offices.